2017
DOI: 10.3345/kjp.2017.60.12.395
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gonadotropin-releasing hormone agonists on anthropometric change in girls with central precocious puberty

Abstract: PurposeThe potential effect of gonadotropin-releasing hormone agonist (GnRHa) treatment on the weight of girls with central precocious puberty (CPP) remains a controversy. We investigated anthropometric changes during and after GnRHa treatment among girls with CPP.MethodsThis retrospective study evaluated data from 127 girls with CPP who received GnRHa treatment for ≥2 years. Height, weight, and body mass index (BMI) values were compared at the baseline (visit 1), after 1 year of GnRHa treatment (visit 2), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
2
15
0
2
Order By: Relevance
“…In this study, GnRHa treatment significantly increased BMI and BMI SDS in both groups over 1 year of GnRHa treatment, which was in concordance with previous studies. 26,28) However, there was no significant difference in change of BMI SDS regardless of type of GnRHa.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 83%
See 4 more Smart Citations
“…In this study, GnRHa treatment significantly increased BMI and BMI SDS in both groups over 1 year of GnRHa treatment, which was in concordance with previous studies. 26,28) However, there was no significant difference in change of BMI SDS regardless of type of GnRHa.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 83%
“…There has been controversy about the association between GnRHa treatment and weight gain or obesity [ 24 ]. Several studies have shown increased BMI SDS during GnRHa treatment and decreased BMI SDS after discontinuation of GnRHa [ 25 - 28 ]. In a study with a 1-month GnRHa depot formulation, the proportion of normal weight, overweight, and obese subjects did not differ significantly before and after discontinuation of GnRHa treatment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations